ASSESSING INVESTMENT REQUIREMENTS TO ATTAIN A 7% ECONOMIC GROWTH RATE IN BANDUNG REGENCY BY 2030 - Daniel Simamora (RADJA PUBLIKA, 2025)
Achieving the ambitious economic growth targets mandated in the Bandung Regency's Regional Medium-Term Development Plan (RPJMD) requires a solid investment planning foundation. This study aims to examine the investment needs required to drive the acceleration of regional economic growth until 2030. Using a quantitative approach through Incremental Capital-Output Ratio (ICOR) analysis based on historical GRDP and GFCF data, this research measures the level of investment efficiency and projects the required capital amount. The analysis results indicate that Bandung Regency has a reasonably good level of investment efficiency. However, to achieve the established economic growth targets, a significant increase in investment volume beyond historical realization is necessary. This finding implies that the regional development strategy must focus on two main pillars: not only attracting large volumes of investment but also maintaining and enhancing investment efficiency (keeping the ICOR low) through improvements in the business climate, human capital quality, and directing investment towards high-value-added sectors.